Promoting landfill mining for sustainable resource recovery, circular economy, and climate mitigation: a review - Goh, Kai Chen; Kurniawan, Tonni Agustiono; Othman, Mohd Hafiz Dzarfan; Jumaniyozov, Khurmatbek; Aziz, Faissal; Anouzla, Abdelkader; Ali, Imran; Khan, M. Imran; Alsultan, G. Abdulkareem; Zhang, Dongdong; Abass, Kasim Sakran; Wong, Hin Yong; et al. (Frontiers in Environmental Science, 2025)
Recently, landfill mining (LFM) has emerged as a promising strategy for addressing the challenges of waste management, resource recovery, and climate change mitigation. This work explores the potential of landfill mining to transform traditional landfills from environmental liabilities into assets. By recovering nutrients, energy, and materials from landfill leachate, landfill mining can reduce greenhouse gas (GHG) emissions, particularly methane (CH4), while contributing to the circular economy. This study evaluates the technologies applied in landfill mining, such as bioreactors, anaerobic digestion, and leachate recirculation, based on published literature from 2000 to 2025, focusing on their value in resource recovery. More specifically, this study aims at recovering renewable CH4 energy from leachate and extracting macro-nutrients such as nitrogen (N), phosphorus (P), and potassium (K) which can be turned into commercial fertilizers. This study further analyzes the advantages of landfill mining, which include reducing CH4 emissions by up to 30% and the potential energy value of 15 GWh from 1.5 million m3 of CH4. The study also explores the socio-economic consequences of landfill mining, focusing on employment opportunities, improved waste management systems, and enhanced local community welfare. Additionally, this work discusses the technological, financial, and regulatory challenges that hinder the widespread adoption of landfill mining for promoting circular economy. Finally, this work calls for further investment, research, and policy development to unlock the full potential of landfill mining as a sustainable waste management strategy and a key contributor to resource recovery in the circular economy paradigm.